Corrugated carbon/epoxy composite bipolar plate for vanadium redox flow batteries. (January 2015) - Choe, Jaeheon; Kim, Ki Hyun; Lee, Dai Gil
Abstract: As the consumption of electricity has increased continuously, risk management of power outages has become an important issue. Energy storage systems have been proposed as a solution, which efficiently manage electricity by storing it during non-peak time and subsequently providing it during peak time. The vanadium redox flow battery (VRFB) is one of the safest and most durable energy storage systems, due to its unlimited capacity and non-flammability without explosion in comparison to other energy storage systems. However, the efficiency of the VRFB largely depends on the performance of bipolar plates (BPs), especially the shape of the BPs, which affects the flow of electrolyte and the surface area of electrodes. Therefore, optimizing the shape of the BPs for VRFBs is necessary. In this study, a corrugated carbon/epoxy composite bipolar plate (CCBP) for VRFBs was designed to increase the efficiency of the electrolyte flow and decrease the area-specific resistance (ASR) of the CCBP. The shape of the corrugations in the CCBP was optimized to decrease both the ohmic and pumping losses in the VRFB stack. Finally, the designed CCBP was developed and tested by the ASR measurement and electrolyte flow.